Previous experience of a video game player and its effects on video game development - Tuominen, Oskari (My University, 2025)
This thesis presents what kind of effect the video game player’s previous experience with video games has with their performance in new video games, as well as how does the current video game development industry take this into account in their game design. The insight from this research can be used to make video games more accessible, balanced, and enjoyable experience for players of all backgrounds. To find out the effect of the video game player’s previous experience, we conducted an experiment using a video game as a testing tool. This game benchmarked the performance of the participants in the session, and we then compared the results to the participants’ previous gaming experience. The results of the test game showed that seasoned video game players performed better than inexperienced players when playing new video games. This thesis also includes interviews with several video game development companies, where the game design dimension was viewed from the perspective of previous gaming experiences of the player. The companies reported to take the player’s previous gaming experience into account in their game design and testing, and how one of the most difficult aspects in game design is balancing the difficulty to the player base possessing differing experience levels in video games. Based on the findings of the thesis, video game design should be adjusted to accommodate players off all skill levels and types by having a varied tester base in the testing process of the game. Game developers should also take advantage of experienced players capability of performing well in video games they have not played before in their game design choices.
Keywords: game design, video game, flow, player type